PENGARUH FAKTOR GOOD CORPORATE GOVERNANCE DAN FREE CASH FLOW TERHADAP MANAJEMEN LABA PADA PERUSAHAAN TRANSPORTASI DI ASIA TENGGARA - Sunaryo, Deni (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of good corporate governance and free cash flow on earnings management. Good Corporate Governance factors used in this study are the size of the audit committee, independent board of commissioners, institutional ownership, and managerial ownership. Earnings management value is measured using discretionary accruals. The research sample is 12 transportation companies listed on the Southeast Asian Stock Exchange which were selected through purposive sampling in the 2014-2018 period. Data were analyzed based on multiple linear regression. Based on the test results, it can be concluded that the good corporate governance factors (audit committee size, independent board of commissioners, institutional ownership, managerial ownership) and free cash flow have no significant effect on earnings management, either partially or simultaneously.